Associations between neighborhood built, social, or toxicant conditions and child externalizing behaviors in the Detroit metro area: a cross-sectional study of the neighborhood ‘exposome’ - Amber L. Pearson; Elizabeth A. Shewark; S. Alexandra Burt (BMC Public Health, 2022)
Abstract Background The specific ‘active ingredients’ through which neighborhood disadvantage increases risk for child psychopathology remains unclear, in large part because research to date has nearly always focused on poverty to the exclusion of other neighborhood domains. The objective of this study was to evaluate whether currently assessed neighborhood built, social, or toxicant conditions were associated with child externalizing psychopathology outcomes separately, and in a combined model, using data from the Detroit-metro county area. Methods We conducted principal components analyses for built, social, or toxicant conditions. Next, we fitted separate multiple regression models for each of the child externalizing psychopathology measures (oppositional defiant and conduct problems) as a function of built, social, or toxicant components. Results We found that built features (more non-profits, churches, and alcohol outlets, and less agriculture and vacant properties) were associated with conduct problems, while toxicant conditions (high percent industrial, toxins released and number of pre-1978 structures) were associated with oppositional defiance problems. There was no significant association between greenspace or social conditions and child externalizing outcomes. When examined simultaneously, only the significant independent association between built conditions and conduct problems remained. Conclusions Built, social, and toxicant neighborhood conditions are not interchangeable aspects of a given neighborhood. What’s more, built features are uniquely associated with child externalizing outcomes independently of other neighborhood characteristics. Future research should consider how changes in the built conditions of the neighborhood (e.g., development, decay) serve to shape child externalizing behaviors, with a focus on identifying potentially actionable elements.